GAYA KOMUNIKASI ISLAMI PIMPINAN DALAM MENARIK MINAT MASYARAKAT MENYEKOLAHKAN ANAK KE DAYAH MISBAHUR RASYAD ACEH TAMIANG - Mawardi Siregar; Muhammad Mukhlis; Nuriah Nuriah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2022)
The Scholars have emphasized the bulk of studies on communication styles from a general communication perspective. This article looks at the Islamic communication style from a new angle to see how it may help an institution gain public confidence and improve its reputation. The Data was gathered through in-depth interviews with carefully chosen informants, as part of a qualitative study. The collection of interview guidelines is intended to make the interviews more structured and oriented toward the targeted research goals. Additionally, for data collected during the study, repeated observations at the research location are a possibility. To complete the essential data, relevant documents are also used. Using Hamid Mowlana's notion of Islamic communication, this study demonstrates that the leadership's Islamic communication style has an influence on the institution's reputation because leaders and members are able to develop communication that is more dynamic, humanistic, and promotes civility. The results of this study also show that the Islamic communication style can increase public trust in sending their children to the boarding school of Misbahur Rasyad Al-Aziziyah